(untitled) (Fiep Bulletin - online, 2013)
Knowing VO2 Max is the maximum amount of oxygen that can withdraw the body from the atmosphere, the muscles take up and use in the production of energy. To classify the level of VO ² max (ml / kg / min) of the subjects used the framework proposed by Heyward (1977) where it divides by age and sex. Since the objective of this study was to evaluate and verify the VO2 Max of students of Graduate in Physical Education from the University Anhanguera / UNIDERP. To obtain these results we evaluated 39 healthy volunteers, 18 female and 21 male, healthy and physically active. The test performed was the coming and going of 20m. protocol Léger and Lambert (1988). The average results obtained in the test for the 18 learners were; 21.6 years (± 2.2) with the old distance of 573.3 m (± 262.6), obtaining 36 ml / kg / min (± 4, 5) VO2 max is considered "good" because the number of students in 21 were as follows: 22.1 years (± 2.3) of age, distance traveled was 1156.2 m (± 345.1) and VO² max of 45.3 ml / kg / min (± 5.3) considered "Very Good" Therefore we conclude that the population studied, being composed of active and healthy individuals, explains the reason why the average rating VO² Max was "good" and "Very Good".